Determination of soil deformation modulus using the static and dynamic circular plate load test - Tašić Dušan; Đurđevac-Ignjatović Lidija; Ignjatović Dragan; Đurđevac Vanja; Softić Sead (Mining and Metallurgy Engineering Bor, 2021)
The increase in mining activity in the Bor basin in recent years has also required the construction of new mining facilities. The construction of numerous embankments and dams, as parts of these facilities, required a constant control of compaction the coarse-grained and fine-grained materials from which they were built. The compaction check was performed using the static and dynamic circular plate test. The results of measurement and correlation of static and dynamic deformation modulus for multiple types of materials, used during construction, are presented.